Measuring and explaining the intra-coalition dynamics of coalition governance - Sheldon, C (2023)
Coalition governance, the period between coalition formation and termination, is a critical, yet understudied aspect of a coalition cabinet’s life cycle. The opaque nature of multi-party governance poses significant challenges to understanding its day-to-day operations, and, as a result, existing literature is overly reliant on static, indirect, measurements. Since coalition governance is theorised to be variable and dynamic, this means significant details pertaining to party behaviour remain obscured. This thesis sets out to study the behaviour of political parties in coalition governance by capturing coalition differentiation. Whether coalition parties choose to defend distinct party goals, as opposed to the coalition consensus, marks a conscious departure from a public united front. Since unity is necessary for coalition effectiveness, this can have serious implications for coalition governance itself. The precise role of differentiation in coalition governance is established in three separate articles. The first article applies supervised text classification to measure, dynamically, coalition party differentiation in parliamentary speech. This results in a monthly party measure for 69 cabinets from ten European countries, making it the first comparative measure of differentiation. The second article employs this measure and establishes that differentiation is predominantly displayed by coalition parties with strong bargaining power. The final article considers the purpose of coalition differentiation and thus what one can infer about coalition governance from its variation. The resulting proposition is that parties differentiate to display bargaining power when navigating uncertain bargaining environments, and, in this way, influence coalition negotiations. By measuring differentiating behaviour dynamically, and subsequently establishing its prevalence and purpose in coalition bargaining, this thesis sheds light on the secretive process of coalition governance. Moreover, this novel comparative measure of coalition differentiation enables the dynamic testing of core assumptions which previously have eluded analysis regarding coalition party representation, accountability, electoral performance, and future coalition inclusion.